2010
DOI: 10.1007/s10535-010-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous spermine on sweet sorghum during germination under salinity

Abstract: Seedlings of Sorghum bicolor (L.) Moench were subjected to 180 mM NaCl with or without 0.25 mM spermine (SPM) for 7 d. NaCl treatment resulted in the inhibition of growth and increased the content of free proline, soluble protein and malondialdehyde (MDA). Additionally, it also enhanced the activity of catalase (CAT), peroxidase (POX) in both shoots and roots, while decreased that of glutathione reductase (GR). When exogenous spermine was added to the test solution, the growth of sweet sorghum seedlings was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 23 publications
6
20
0
Order By: Relevance
“…2c). Increase in activity of CAT under conditions of salt stress is in consonance with several earlier observations (Chai et al 2010;Sheokand et al 2008). POD and CAT showed similar level of activity in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2c). Increase in activity of CAT under conditions of salt stress is in consonance with several earlier observations (Chai et al 2010;Sheokand et al 2008). POD and CAT showed similar level of activity in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Transgenic technology is used to develop crop plants tolerant to abiotic stress (Lu et al 2007;Sairam and Tyagi 2004;Sahi et al 2006). Exogenous application of various compounds could help to increase plants resistance to salt stress, such as mannitol in wheat (Seckin et al 2009), spermine in sweet sorghum (Chai et al 2010), nitric oxide, and putrescine in chickpea (Sheokand et al 2008), salicylic acid (SA) in lentil (Misra and Saxena 2009), calcium chloride, and gibberllic acid in linseed (Khan et al 2010), and ascorbic acid in Vicia faba (Younis et al 2010). Conventional breeding is also a major strategy to improve the salt tolerance (Phang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chai et al . () reported that exogenous Spd can alleviate salt stress in sorghum. In the present study, it was also found that exogenous Spd partially alleviated salt‐induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…In the membrane lipids, the double bonds of PUFA moieties are targets of ROS-mediated peroxidation, which damage the membrane structure. The increase in lipid peroxidation has been considered an indicator of oxidative damage in leaves of several plant species subjected to salt stress such as cowpea (Cavalcanti et al 2004(Cavalcanti et al , 2007, rice (Demiral and Türkan 2005), maize (Azevedo-Neto et al 2006) and sorghum (Chai et al 2010). Surprisingly, however, the lipid peroxidation decreased in salt-stressed cashew leaves as indicated by reduction in the TBARS and LPO contents.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%